Discrepancy Evaluation Model (DEM): Analysis of the Implementation of Guidance and Counseling System Support at SMA IT Al-Multazam 2 Linggajati - Nawawi, Erfan; Hidayah, Nur; Wahyuni, Fitri (Journal of Instructional and Development Researches, 2025)
Guidance and Counseling (BK) Evaluation is a process conducted to assess the quality of Guidance and Counseling implementation and ensure that the program is in line with the established objectives. System support includes BK management, professional development for counselors, and collaboration with parents, teachers, and the broader community. This study aims to analyze the gaps in the implementation of system support at SMA IT Al-Multazam 2 Linggajati using the Discrepancy Evaluation Model (DEM). The research method employed is a mixed-methods approach. Quantitative data was collected using a system support evaluation instrument based on a Likert scale of 1-7, which includes 26 statement items, while qualitative data was gathered through in-depth interviews with two BK teachers. The results of the study showed that the implementation of system support at SMA IT Al-Multazam 2 Linggajati had an average score of 176, or 97%, placing it in the very good category. However, qualitative analysis revealed three main issues: (1) administrative workload reducing the intensity of student services, (2) lack of ongoing professional development mechanisms, and (3) collaboration with parents/community that remains reactive.